Influencer Politik dan Penggiringan Opini Publik Isu Fufufafa di Media Sosial X - Vinanda, Rufki Ade; Lokita , Raden Arditya Mutwara (Kinesik, 2024)
The Fufufafa issue became a trending topic on social media X in early September. This issue began with the discovery of a Kaskus account that allegedly belonged to the Vice President of Indonesia, Gibran Rakabuming Raka. Fufufafa went viral because the account made rude insults to President Prabowo Subianto. Political influencers also expressed their opinions on this case through X. Therefore, the author focuses on finding out how political influencers through social media X lead public opinion regarding Fufufafa. Robert N. Entman's framing analysis method will be used by emphasizing the definition of the problem, the cause of the problem, making capital decisions, and recommending certain solutions. The influencers chosen are @Dennysiregar7 and @yusuf_dumdum, who are considered vocal about this issue. This paper finds that there are efforts to lead public opinion on the Fufufafa issue. The X account has been used as a tool to promote a point of view or lead public opinion regarding an issue according to what they believe.